2021
DOI: 10.1016/j.xhgg.2020.100014
|View full text |Cite
|
Sign up to set email alerts
|

Germline mutation in POLR2A: a heterogeneous, multi-systemic developmental disorder characterized by transcriptional dysregulation

Abstract: De novo germline variation in POLR2A was recently reported to associate with a neurodevelopmental disorder. We report twelve individuals harboring putatively pathogenic de novo or inherited variants in POLR2A , detail their phenotypes, and map all known variants to the domain structure of POLR2A and crystal structure of RNA polymerase II. Affected individuals were ascertained from a local data lake, pediatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…She briefly enrolled in college before opting to work a part-time occupation instead. Targeted review of systems, focusing on key clinical features identified by Hansen and colleagues [ 16 ] were negative for ataxia, joint hypermobility, skin abnormalities, recurrent fever of unknown etiology, congenital heart disease, immune dysfunction or developmental dysplasia of the hip.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…She briefly enrolled in college before opting to work a part-time occupation instead. Targeted review of systems, focusing on key clinical features identified by Hansen and colleagues [ 16 ] were negative for ataxia, joint hypermobility, skin abnormalities, recurrent fever of unknown etiology, congenital heart disease, immune dysfunction or developmental dysplasia of the hip.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, Hansen and colleagues identified deleterious POLR2A variants in a cohort of 12 individuals ascertained through an online data lake, a pediatrics clinic and an online community for affected individuals [ 16 ]. Their analysis included one individual who was previously reported by Haijes and colleagues [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a primary 20 and secondary 20,21 cohort of patients was recently identified that carry mutations in POLR2A, the major catalytic subunit of RNAPII in human cells. These patients suffer from muscle weakness, enlarged ventricles, white matter abnormalities and cerebellar problems.…”
Section: Human Patients With Mutations In Polr2amentioning
confidence: 99%
“…Altogether, on the basis of the results of both predictive and functional analyses, eleven variants were classified as probably disease-causing [ 52 ]. Recently, the yeast model for POLR2A variant classification was leveraged to study other cases of individuals with neurodevelopmental syndromes, strengthening the association of POLR2A with this disease [ 53 ].…”
Section: The Study Of Genetic Variation Of Single Genesmentioning
confidence: 99%